Magnetron sputtering of protective coatings on parts of surfaces of products and tools using multielement targets manufactured using a new technology - Berdibekov, A.T.; Laurinas, V.Ch; Dolya, A.V.; Gruzin, V.V.; Guchenko, S.A.; Tvardovsky, A.N. (KU Publ, 2022)
Recently, the use of magnetron sputtering for the deposition of protective coatings has been intensively developed. The great prospect of using this method is due to the possibility of applying high-entropy coatings, which are used to protect surfaces that are simultaneously exposed to elevated temperatures, aggressive media and various types of wear. However, the use of the method of creating high-entropy coatings greatly hinders the absence in many cases of the required alloys, which have not only a certain qualitative elemental composition, but also a quantitative one. We managed to solve this problem by creating multi-element targets, with the help of which it becomes possible to create not only almost any elemental composition, but also to regulate the quantitative composition of elements. In this paper, we have proposed a method for manufacturing new types of targets for magnetron sputtering, with a detailed description of the technological chain of their manufacture. The novelty lies in the possibility of applying multi-element coatings when using one target. This is due to the fact that the number of different elements in the target can be measured in tens. The paper also presents the obtained positive result of using a target, which included five different metals, during magnetron sputtering.
Keywords: magnetron sputtering; protective coating; multi-element targets; high entropy coatings